Baseline choroidal thickness as a short-term predictor of visual acuity improvement following antivascular endothelial growth factor therapy in branch retinal vein occlusion. Issue 1 (22nd March 2018) - Rayess, Nadim; Rahimy, Ehsan; Ying, Gui-Shuang; Pefkianaki, Maria; Franklin, Jason; Regillo, Carl D; Ho, Allen C; Hsu, Jason
Abstract : Purpose: To evaluate the association between subfoveal choroidal thickness (SFCT) and branch retinal vein occlusion (BRVO) eyes treated with antivascular endothelial growth factor (anti-VEGF) therapy. Methods: Retrospective cohort study of treatment naïve BRVO eyes treated with 3 monthly anti-VEGF injections. All patients received enhanced depth imaging spectral-domain optical coherence tomography scans to determine SFCT and central macular thickness (CMT). Baseline predictors (particularly SFCT) for functional response (best-corrected visual acuity (BCVA) gain ≥2 lines) were assessed at 3 months using univariate and multivariate analyses. Results: Forty eyes from 39 patients were included. Mean baseline SFCT was higher in functional responders (240.4±73.1 µm), compared with both non-responders (193.3±63.6 µm; p=0.036) and their corresponding fellow eye (202.2±67.1 µm; p=0.022). A higher baseline SFCT (for every 100 µm increase in SFCT) was found to be a positive predictor for functional response (regression coefficient: 1.1; p=0.03) on univariate analysis but not multivariate analysis. A worse baseline BCVA (for every 0.1 logMAR increase) was a positive predictor for visual improvement with an adjusted OR of 1.30 (95% CI 1.03 to 1.63; p=0.0009) on multivariate analysis. Conclusions: Patients with BRVO with a worse initial BCVA are most likely to achieve visual improvement following anti-VEGF therapy. Additionally, baseline SFCT may also help predict which patients with BRVO have favourable visual outcomes. Patients with an initial choroidal thickness thicker than their fellow eye are more likely to have short-term visual improvement following treatment.